Penerapan Model Cooperatif Tipe Jigsaw Berbantuan Media Pop Up Book Terhadap Hasil Belajar Siswa Pada Pembelajaran IPAS - Sindi Giftinnisa; Supriyanto; Eka Lokaria (STAI AL-AMIN, 2025)
This study aims to determine the results of learning science of class V students of SD Negeri 59 Lubuklinggau after the implementation of the Jigsaw Type Cooperative Model Assisted by Pop Up Book Media significantly achieved KKTP. The method used is a pre-experimental research method with a Pre-test and Post-test experimental design. The sample was taken from a population consisting of two classes, namely class VA and VB, with a total of 39 students then a draw was carried out between class VA and VB, so that the sample was VA making it the sample in this study, the research instrument in the form of 5 essay questions. Based on the analysis of the pre-test and post-test conducted, there was a significant achievement in the results of learning science of class VA students of SD Negeri 59 Lubuklinggau after implementing the Jigsaw Type Cooperative Model Assisted by Pop Up Book Media. The average initial ability (pre-test) of students was 48.47 increasing to 68.47 in the final ability test (post-test). This study shows significant results in the achievement of student learning outcomes, as seen from the results of statistical analysis that reject the null hypothesis, and achieve learning objectives with the Jigsaw Type Cooperative Model Assisted by Pop Up Book Media, through group learning that can improve learning outcomes.